Effects of chronic light cycle disruption during adolescence on circadian clock, neuronal activity rhythms, and behavior in mice - Bonilla, Pablo; Shanks, Alexandria; Nerella, Yatin; Porcu, Alessandra (Frontiers in Neuroscience, 2024)
The advent of artificial lighting, particularly during the evening and night, has significantly altered the predictable daily light and dark cycles in recent times. Altered light environments disrupt the biological clock and negatively impact mood and cognition. Although adolescents commonly experience chronic changes in light/dark cycles, our understanding of how the adolescents’ brain adapts to altered light environments remains limited. Here, we investigated the impact of chronic light cycle disruption (LCD) during adolescence, exposing adolescent mice to 19hr of light and 5hr of darkness for 5 days and 12L:12D for 2 days per week (LCD group) for 4 weeks. We showed that LCD exposure did not affect circadian locomotor activity but impaired memory and increased avoidance response in adolescent mice. Clock gene expression and neuronal activity rhythms analysis revealed that LCD disrupted local molecular clock and neuronal activity in the dentate gyrus (DG) and in the medial amygdala (MeA) but not in the circadian pacemaker (SCN). In addition, we characterized the photoresponsiveness of the MeA and showed that somatostatin neurons are affected by acute and chronic aberrant light exposure during adolescence. Our research provides new evidence highlighting the potential consequences of altered light environments during pubertal development on neuronal physiology and behaviors.